Trapping methods for capturing the screwworm Telchin atymnius (Dalman, 1824) in plantain plantations (Musa AAB) (2020)
The larval stage of the screwworm (Telchin atymnius) inflicts damage on the pseudostem and corm, allowing other pests and pathogens to affect the crop and decrease fruit yield and quality. The adults of these insects are attracted to certain colors and types of food, and their capture reduces oviposition and damage from future larvae. The objective of this study was to evaluate the efficacy of capturing adult individuals in plantain farms through two experiments: a) using traps with different colors (blue, white, and transparent) and b) using two types of traps (the most efficient color trap of the prior experiment and an artisanal trap). A completely randomized experimental design was used. The insects were recorded through counting, and their binomial negative, Poisson, and zero-inflated variations were utilized for data analysis. Furthermore, temperature and rainfall variables were included as statistical model parameters of the color trap experiment. The parameters were considered significant when P<0.05. The number of individuals captured with the blue and white traps were 2.84 and 1.38 times higher than the numbers captured with the transparent trap, respectively. In addition, there were 6.26 times more captures in months with higher temperatures compared to months with lower temperature. With the artisanal trap, there were 4.33 times more captures compared to the blue trap; it was also the cheapest trap. The use of blue traps (bags) with toxic bait or traps with molasses bait is a viable alternative for monitoring and capturing in the integrated management of the insect.